2013
DOI: 10.2478/hukin-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Motion Analysis of Turns Performed by Highly Ranked Viennese Waltz Dancers

Abstract: Twenty-four dance couples performing at the 2011 IDSF (International DanceSport Federation) International Slovenia Open were divided into two groups: the first twelve placed couples (top ranked) and the last twelve placed couples (lower ranked). Video recordings were processed automatically using computer vision tracking algorithms under operator supervision to calculate movement parameters. Time and speed of movement were analysed during single natural (right) and reverse (left) turns performed during the Vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Furthermore, in youth category the choreography becomes more complex and physically challenging as the frequency and speed of turns and hip movements is increased compared to junior category. This can be partly supported by previous research that showed significant differences in velocity between lower and higher rank dancers [35]. Apparently, no significant age-class or gender differences were observed for absolute dancing hours and percentage of dancers performing strength training to meet these increased physical demands, growth and strength imbalances.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, in youth category the choreography becomes more complex and physically challenging as the frequency and speed of turns and hip movements is increased compared to junior category. This can be partly supported by previous research that showed significant differences in velocity between lower and higher rank dancers [35]. Apparently, no significant age-class or gender differences were observed for absolute dancing hours and percentage of dancers performing strength training to meet these increased physical demands, growth and strength imbalances.…”
Section: Discussionsupporting
confidence: 70%
“…DanceSport consists of three different disciplines: Standard dances (Waltz, Tango, Viennese Waltz, Slow Foxtrot, and Quickstep), Latin-American dances (Samba, Cha-Cha-Cha, Rumba, Paso Doble, and Jive) and Ten Dances (five Standard and five Latin-American dances). A dancer’s success is determined by technical and tactical skills (Uznović and Kostić, 2005; Howard, 2007; Uznović, 2008; Laird, 2009) morphological and motor abilities (Koutedakis, 2008; Lukić et al, 2011; Prosen et al, 2013), psychological preparation and aesthetics of movement (Lukić et al, 2009; Čačković et al, 2012). Furthermore, efficiency in DanceSport has been suggested as a determining factor for a judge to award marks for the dancers’ performance (Bijster, 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The footage was transferred to a PC post event and analysed with a semi-automated tracking system, which is a large scale human tracking motion measurement system based on computer vision technology (Perš, Bon, Kovačič, Šibila, & Dežman, 2002). The system proved to be suitable for analysing dancers' motion in LA and BR dance (Prosen et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has suggested that in standard dance the speed and distance covered by dancers is most likely to be due to the choreography (Zaletel et al, 2010b) and also due to different level of performance -better couples are faster and travel further distance (Prosen, 2013), but this remains to be determined through motion analysis in Latin-American dance. To authors knowledge partnering skills in Latin-American dance was not often investigated in sports science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation